Modeling seismic activity and its relationship to the physical characteristics of Iraqi governorates (Journal of the College of Basic Education, 2025)
The research presents an analysis of recent recording data issued by the Iraqi Seismic Monitoring Network, the General Authority for Meteorology and Seismic Monitoring, and the Seismic Monitoring Department, for seismic activity in Iraqi governorates for the years (2021-2022-2023 and eight months of 2024) to reveal the dimensions and characteristics of the data. Iraq's location lies between latitudes 29°5 - 37°22' north and longitudes 38°42 - 48°45' east. With an area of ​​435,052 square kilometers, this wide extension led to the contrast in its natural characteristics between the north, the sudden south and the west, and according to this contrast that led later and did not come out until it showed the Iraqi governorates, The inductive approach, moving from part to whole, and the quantitative approach were used to analyze data and represent outcomes. The objective analytical approach was also used to interpret the results. The results were analyzed using analysis tools and modeled using specialized software in geographic information systems. In addition to the statistical analysis by extracting the minimum, maximum, mean and standard deviation of the depth and intensity of the earthquake for each month and each year for the same period, the results focused on the relationship between the frequency of earthquakes in the border provinces between the Iranian side on the one hand and the Turkish side on the other hand, with their occurrence near and far from urban areas, the most severe in measuring the density, depth and intensity of earthquakes on the Richter scale during the time period adopted for the study. Most earthquakes in Iraq are of low to moderate intensity, and destructive earthquakes above 6 degrees are rare. Seismic activity is frequent but often not alarming in terms of danger, except in rare cases Modeling, seismic activity, natural characteristics, Iraqi governorates